Mesenchymal stem cell therapy in eosinophilic granulomatosis with polyangiitis-related lower limb gangrene: a case report - Hui Wang; Qian Zhang; Sensen Wu; Dikang Pan; Yachan Ning; Cong Wang; Jianming Guo; Yongquan Gu (Stem Cell Research & Therapy, 2024)
Abstract Background Eosinophilic granulomatosis with polyangiitis (EGPA), a rare but life-threatening systemic vasculitis, is distinguished by marked eosinophilia and presents with diverse symptoms, including asthma, cutaneous purpura, ecchymosis, skin necrosis, cardiac lesions, peripheral neuropathy, and necrotizing vasculitis. The etiology of EGPA involves a complex interaction among humoral, adaptive, innate, and allergic immune responses. Standard treatment employs prolonged high-dose glucocorticoid therapy, which is critical for survival; however, some patients’ symptoms cannot be relieved. Case report This case report details the medical management of an 11-year-old patient with EGPA, who was at risk of bilateral lower limb amputation due to differential arterial occlusion and severe, necrotizing vasculitis-induced gangrene in both feet. Treatment modalities administered included systemic infusion of Umbilical Cord Mesenchymal Stem Cells (UC-MSCs), targeted gastrocnemius muscle injections, and application of a Placenta-Derived Mesenchymal Stem Cells (PD-MSCs) hydrogel. Results After receiving a four-month regimen of allogeneic mesenchymal stem cell therapy via intravenous and local administration, the patient showed normalized eosinophil counts, reestablished blood flow in the dorsal arteries, and marked improvement in foot ulcerations. Conclusion Mesenchymal stem cell therapy is a promising option for severe EGPA cases refractory to glucocorticoids.